Atividade larvicida e adulticida do extrato etanólico bruto de Deguelia rufescens var. urucu (Ducke) A. M. G. Azevedo em Aedes (Stegomyia) aegypti (Linnaeus, 1762) (Diptera: Culicidae) - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2021)
This study evaluated the activity of crude ethanol extracts from the roots of Deguelia rufescens var. urucu (Fabaceae), a plant popularly known as “ timbó”, in the Amazon region,used in fisheries by indigenous people, due to a chemical substance called rotenone foundin its roots. The objective of this work was to obtain and identify the main classes of secondary metabolites of the crude ethanol extract from the roots of D. rufescens var. urucuand to evaluate its larvicidal and adulticidal activity against the Aedes aegypti mosquito. The roots of D. rufescens var. urucu were collected in the municipality of Macapá-Amapá-Brasil.The Crude Extract was extracted using the exhaustive maceration technique using 70º ethanol as a solvent. From a stock solution of 10,000 ppm (parts per million) different test solutions were prepared(10 ppm, 20 ppm, 30 ppm and 40 ppm) of the crude extract. For larvicidal action of crude ethanol extract of D.rufescens var. annatto, in 24 hours, an 84% mortality was found at concentrations of 40 ppm and 62% at concentrations of 30 ppm and 58.4% at concentrationsof 20 ppm. In 48 hours of exposure this value went to 98.4% at concentrations of 40 ppm and 92% at concentrations of 30ppm and 86.5% at concentrations of 20 ppm. Through the larvicide tests it was possible to establish LC50= 12.53 ppm (-2.97 - 18.28) and LC90= 26.92ppm (20.90 - 47.90). For adulticidal action, the highest mortalities were observed at the concentrations at 80ppm, which was 67.5%, and at the concentration at 100ppm, which hada mortality rate of 96.25% in 24 hours of exposure. From the results of the adulticide test it was possible to establish a LC50 = 46.69 ppm (37.45 - 58.96) and LC90 = 94.4 ppm (76.2 - 127.6) and their respective confidence intervals with the lower limits and higher, showing anactivity that is toxic to adults of A. aegypti. Thus, the crude ethanol extract of D.rufescens var. annatto, showed larvicidal and adulticidal activity against A. aegypti, further studies willhelp to better understand this activity.
Keywords: Aedes aegypti; Deguelia rufescens var; Larvicida natural; CNPQ::CIENCIAS BIOLOGICAS::PARASITOLOGIA